Cobalt transition metal coordination polymer and preparation method and application thereof

By using cobalt transition metal coordination polymer as a photocatalyst, the complex and complicated and costly treatment of dye wastewater in the prior art is solved, and the efficient photocatalytic degradation of organic pollutants in the water is achieved, with good stability and repetition Usage rate.

CN119390996AActive Publication Date: 2025-02-07SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING

Patent Information

Application Number
CN202411527880.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The prior art has problems of complex and complicated pre-treatment and high cost when treating dye wastewater, and it is difficult to effectively remove organic pollutants in the water.

Method used

Cobalt transition metal coordination polymer is used as the photocatalyst to catalyze the degradation of organic pollutants in water under ultraviolet light irradiation. The chemical formula of this material is [Co(L)(2,2-biby)·2H2O]n, belongs to the orthogonal crystal system, P212121 space group, and has good photocatalytic properties.

Benefits of technology

It can achieve photocatalytic degradation rates of algae B, amaranth and naphthol green within 20 minutes under ultraviolet light, and can reach 93.5%, 38.1% and 36.1% respectively under ultraviolet light, and have high reuse rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390996A_ABST
    Figure CN119390996A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt transition metal coordination polymer as well as a preparation method and application thereof, and belongs to the technical field of metal organic complex material photocatalysts, the chemical formula of the cobalt transition metal coordination polymer is [Co (L) (2, 2-biby). 2H2O] n, L is 2-(3-carboxyl phenyl)-6-carboxyl benzimidazole, and n is 1-3. 2, 2, 2-biby is 2, 2 '-dipyridyl; n represents the degree of polymerization and is a positive integer; the cobalt transition metal coordination polymer belongs to a P212121 space group of an orthorhombic crystal system. According to the cobalt transition metal coordination polymer and the preparation method and application thereof, the cobalt transition metal coordination polymer can serve as a photocatalyst, has good photocatalytic performance and can serve as a potential photocatalyst to catalyze and degrade organic pollutants in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal organic complex material photocatalysts, and in particular to a cobalt transition metal coordination polymer and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry worldwide, a large amount of high-concentration dye wastewater discharged in the pharmaceutical, printing and other industries that does not meet the standards has become one of the main sources of water pollution. Due to the relatively stable structure of dyes and the continuous increase in emissions, the treatment of dye wastewater has always been a huge challenge facing mankind. At present, technologies including adsorption, separation, chemical oxidation, flocculation, and photocatalytic degradation are used to effectively remove dyes from wastewater, but there are defects such as complex and cumbersome pre-treatment and high costs. As an emerging technology that has developed rapidly in recent years, photocatalytic degradation has received widespread attention from the world in removing pollutants from wastewater because it can utilize sustainable and inexhaustible solar energy and promote reactions under mild conditions. Semiconductor photocatalysts can be directly driven by light and are considered to be an ideal technology for treating environmental pollution.

[0003] Metal-organic complex materials (CPs) have significant advantages such as large specific surface area, high stability, and easy modification of structure and performance, and have potential application prospects in many fields such as heterogeneous catalysis, gas storage and separation, and sensor detection. In recent years, studies have shown that some CPs exhibit good semiconductor properties under ultraviolet or visible light irradiation, and compared with traditional inorganic semiconductors, CPs have the following significant advantages: open metal active sites, unsaturated metal coordination centers, and adjustable photoelectric properties of organic linkers, indicating that CPs can be used as photocatalysts for photocatalytic degradation of dye wastewater. Summary of the invention

[0004] The purpose of the present invention is to provide a cobalt transition metal coordination polymer and a preparation method and application thereof. The cobalt transition metal coordination polymer can be used as a photocatalyst, has good photocatalytic performance, and can be used as a potential photocatalyst to catalytically degrade organic pollutants in water.

[0005] To achieve the above object, the present invention provides a cobalt transition metal coordination polymer, the chemical formula of the cobalt transition metal coordination polymer is: [Co(L)(2,2-biby)·2H2O] n ;

[0006] Wherein, L is 2-(3-carboxyphenyl)-6-carboxybenzimidazole; 2,2-biby is 2,2'-bipyridine; n represents the degree of polymerization, which is a positive integer; and the cobalt transition metal coordination polymer belongs to the orthorhombic system and the P212121 space group.

[0007] Preferably, the basic structural unit of the cobalt transition metal coordination polymer includes a metal Co 2+ , 1 coordinated 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 1 coordinated 2,2'-bipyridine, and 2 coordinated water molecules; 2-(3-carboxyphenyl)-6-carboxybenzimidazole adopts a monodentate coordination mode with the metal Co through the carboxyl groups at both ends 2+ Coordination, 2,2'-bipyridine with metal Co 2+ Bidentate chelate coordination, water molecules adopt monodentate coordination mode with metal Co 2+ Coordination.

[0008] Preferably, 1 metal Co 2+ Denoted as Co1, it forms a six-coordinated deformed octahedral configuration with two coordinated oxygen atoms O2 and O3A of two 2-(3-carboxyphenyl)-6-carboxybenzimidazoles, two coordinated nitrogen atoms N1 and N2 of one 2,2'-bipyridine, and two coordinated water molecules O1W and O2W; O3A, O2, N1 and N2 occupy the four equatorial vertices of the deformed octahedral configuration, and O1W and O2W occupy the two vertex positions of the deformed octahedral configuration; the bond length of Co-O in the deformed octahedral configuration is The bond length of Co-N is The bond angle of O-Co-O is 85.25(9)~171.61(10)°, and the bond angle of O-Co-N is 90.36(10)~173.28(10)°.

[0009] Preferably, the adjacent metal Co 2+ By connecting with 2-(3-carboxyphenyl)-6-carboxybenzimidazole ligands, a 1D chain structure is formed, and the 1D chain structure is expanded into a three-dimensional network structure through weak interaction forces.

[0010] Preferably, the weak interaction force is one or more of π-π stacking, OH...O hydrogen bonding, OH...N hydrogen bonding and CH...O hydrogen bonding.

[0011] The present invention also provides a method for preparing a cobalt transition metal coordination polymer, which is characterized by comprising the following steps:

[0012] S1. Dissolve 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 2,2'-bipyridine and Co(NO3)2·4H2O in deionized water and acetonitrile, and stir in a sealed container at room temperature;

[0013] S2. Add NaOH to adjust pH to 5-7 and continue stirring for 25-35 minutes;

[0014] S3, transferring the obtained suspension to a polytetrafluoroethylene reactor, covering it with an inner cover and placing it in a high-pressure stainless steel reactor, heating the high-pressure reactor in a programmable temperature-controlled oven and keeping it warm for culturing;

[0015] S4, the reaction solution was heated at 3-7℃·h -1 The reaction mixture is cooled to room temperature at a rate of , and a cobalt transition metal coordination polymer is obtained.

[0016] Preferably, the molar ratio of 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 2,2'-bipyridine and Co(NO3)2·4H2O in S1 is 1:0.5:1-1:3:4, and the sealed stirring time is 25-35 min.

[0017] Preferably, the high pressure reactor in S3 is heated to 100-140° C. and the heat preservation and culturing time is 36-72 h.

[0018] The present invention also provides an application of a cobalt transition metal coordination polymer, wherein the cobalt transition metal coordination polymer described above is applied to photocatalytic degradation of organic pollutants in water.

[0019] Therefore, the present invention adopts the above-mentioned cobalt transition metal coordination polymer and its preparation method and application, which have the following beneficial effects:

[0020] 1. The cobalt transition metal coordination polymer prepared by the present invention can maintain stability within 200°C.

[0021] 2. The cobalt transition metal coordination polymer prepared by the present invention can be used as a photocatalyst to degrade organic pollutants in water. Under ultraviolet light irradiation, the photocatalytic degradation rate of erythrophyll B is 93.5% within 20 minutes, the photocatalytic degradation rate of amaranth is 38.1%, and the photocatalytic degradation rate of naphthol green is 36.1%.

[0022] 3. The cobalt transition metal coordination polymer photocatalyst prepared by the present invention has a high reuse rate for degrading organic pollutants.

[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a cobalt complex coordination environment diagram of a cobalt transition metal coordination polymer and its preparation method and application example of the present invention;

[0025] Figure 2 It is a cobalt transition metal coordination polymer and its preparation method and application example of the present invention, and the cobalt complex 1D chain structure;

[0026] Figure 3This is a thermogravimetric analysis diagram of a cobalt complex of a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention;

[0027] Figure 4 It is an X-ray powder diffraction diagram of experimental test and computer simulation of a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention;

[0028] Figure 5 This is an infrared spectrum of a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention;

[0029] Figure 6 It is a cobalt transition metal coordination polymer of the present invention and its preparation method and application example 1, an ultraviolet spectrum of the green photocatalytic degradation of naphthol;

[0030] Figure 7 This is a UV spectrum of a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention on photocatalytic degradation of amaranth red;

[0031] Figure 8 This is an ultraviolet spectrum of a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention on photocatalytic degradation of erythrophycoerythrophyll B;

[0032] Fig. 9 It is a bar graph of the catalytic degradation of different organic dyes (erythrosin B, amaranth, naphthol green) by a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention;

[0033] Fig.10 It is a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention. The catalytic mechanism (TBA, BQ and AO) of phycoerythrocyanine B was tested and the test results are bar graph;

[0034] Fig.11 It is a comparison diagram of the catalytic degradation of erythrophycoerythrophyll B by different capture agents (TBA, BQ and AO) of a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention;

[0035] Fig.12 This is a diagram showing the kinetic test results of catalytic degradation of erythrophycoerythrophyll B under different capture agents (TBA, BQ and AO) in Example 1 of a cobalt transition metal coordination polymer and its preparation method and application in the present invention;

[0036] Fig.13 This is a graph showing the test results of the repeated use of a cobalt transition metal coordination polymer and its preparation method and application example 1 of the present invention for catalytic degradation of erythrophycoerythrophyll B. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0039] Example

[0040] The present invention provides a cobalt transition metal coordination polymer, the chemical formula of the cobalt transition metal coordination polymer is: [Co(L)(2,2-biby)·2H2O] n ; Wherein, L is 2-(3-carboxyphenyl)-6-carboxybenzimidazole; 2,2-biby is 2,2'-bipyridine; n represents the degree of polymerization, which is a positive integer; the cobalt transition metal coordination polymer belongs to the orthorhombic system and the P212121 space group.

[0041] The basic structural unit of cobalt transition metal coordination polymers consists of a metal Co 2+ , 1 coordinated 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 1 coordinated 2,2'-bipyridine, and 2 coordinated water molecules; 2-(3-carboxyphenyl)-6-carboxybenzimidazole adopts a monodentate coordination mode with the metal Co through the carboxyl groups at both ends 2+ Coordination, 2,2'-bipyridine with metal Co 2+ Bidentate chelate coordination, water molecules adopt monodentate coordination mode with metal Co 2+ Coordination.

[0042] 1 metal Co 2+ Denoted as Co1, it forms a six-coordinated deformed octahedral configuration with two coordinated oxygen atoms O2 and O3A of two 2-(3-carboxyphenyl)-6-carboxybenzimidazoles, two coordinated nitrogen atoms N1 and N2 of one 2,2'-bipyridine, and two coordinated water molecules O1W and O2W; O3A, O2, N1 and N2 occupy the four equatorial vertices of the deformed octahedral configuration, and O1W and O2W occupy the two vertex positions of the deformed octahedral configuration; the bond length of Co-O in the deformed octahedral configuration is The bond length of Co-N is The bond angle of O-Co-O is 85.25(9)~171.61(10)°, and the bond angle of O-Co-N is 90.36(10)~173.28(10)°.

[0043] Adjacent metal Co 2+A 1D chain structure is formed by connecting with 2-(3-carboxyphenyl)-6-carboxybenzimidazole ligands, and the 1D chain structure is expanded into a three-dimensional network structure through weak interaction forces. The weak interaction forces are one or more of π-π stacking, OH...O hydrogen bonds, OH...N hydrogen bonds and CH...O hydrogen bonds.

[0044] The three-dimensional network structure can provide stronger mechanical strength and stability. Compared with a single 1D chain structure, the three-dimensional network structure can better resist the effects of external forces, and the three-dimensional network structure can enable the material to maintain its structural integrity at high temperatures and is not prone to decomposition or phase change. The three-dimensional network structure usually has a higher specific surface area, which makes the material exhibit excellent performance in catalysis, adsorption and gas storage. A larger specific surface area means more active sites, thereby improving the reaction efficiency and adsorption capacity of the material.

[0045] The three-dimensional network structure can stabilize the coordination environment through weak interaction forces and reduce the impact of external conditions on the material, which helps to improve the stability of the material in various chemical environments. The three-dimensional network structure can provide more active sites, and these active sites can be regulated by weak interaction forces. This makes the material show higher activity and selectivity in catalytic reactions.

[0046] The present invention also provides a method for preparing a cobalt transition metal coordination polymer, which is characterized by comprising the following steps:

[0047] S1. Dissolve 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 2,2'-bipyridine and Co(NO3)2·4H2O in deionized water and acetonitrile at a molar ratio of 1:1.5:2, and stir for 25-35 minutes under sealed condition at room temperature. The preparation of cobalt transition metal coordination polymers using 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 2,2'-bipyridine and Co(NO3)2·4H2O not only provides structural diversity and controllability, but also enhances the stability, porosity and specific surface area of ​​the materials.

[0048] S2. Add NaOH to adjust pH to 5-7 and continue stirring for 25-35 minutes;

[0049] S3, transferring the obtained suspension to a polytetrafluoroethylene reactor, covering it with an inner cover and placing it in a high-pressure stainless steel reactor, heating the high-pressure reactor to 100-140° C. in a programmable temperature-controlled oven and keeping it warm for 36-72 hours;

[0050] S4, the reaction solution was heated at 3-7℃·h -1 The reaction mixture is cooled to room temperature at a rate of , and a cobalt transition metal coordination polymer is obtained.

[0051] Example 1

[0052] A cobalt transition metal coordination polymer, the chemical formula of which is [Co(L)(2,2-biby)·2H2O] n , obtained by the following steps:

[0053] 0.01 mol of 2-(3-carboxyphenyl)-6-carboxybenzimidazole L, 0.015 mol of 2,2'-bipyridine, 0.02 mol of Co(NO3)2·4H2O, 5 mL of deionized water and 5 mL of acetonitrile were mixed evenly, sealed and stirred for 30 min at room temperature, pH was adjusted to 5 with 0.5 mol / L NaOH, and stirred for another 30 min. The obtained suspension was transferred to a polytetrafluoroethylene reactor (25 mL), covered with an inner cover and placed in a high-pressure stainless steel reactor. The high-pressure reactor was heated to 140°C in a programmable temperature-controlled oven and kept warm for 72 hours. The reaction solution was then heated at 5°C·h -1 The mixture was cooled to room temperature at a rate of to obtain a cobalt transition metal coordination polymer.

[0054] Example 2

[0055] A cobalt transition metal coordination polymer, the chemical formula of which is [Co(L)(2,2-biby)·2H2O] n , obtained by the following steps:

[0056] 0.02 mol of 2-(3-carboxyphenyl)-6-carboxybenzimidazole L, 0.03 mol of 2,2'-bipyridine, 0.04 mol of Co(NO3)2·4H2O, 10 mL of deionized water and 10 mL of acetonitrile were mixed evenly, sealed and stirred for 30 min at room temperature, pH was adjusted to 6 with 0.5 mol / L NaOH, and stirred for another 30 min. The obtained suspension was transferred to a polytetrafluoroethylene reactor (25 mL), covered with an inner cover and placed in a high-pressure stainless steel reactor. The high-pressure reactor was heated to 140°C in a programmable temperature-controlled oven and kept warm for 72 hours. The reaction solution was then heated at 5°C·h -1 The mixture was cooled to room temperature at a rate of to obtain a cobalt transition metal coordination polymer.

[0057] Example 3

[0058] A cobalt transition metal coordination polymer, the chemical formula of which is [Co(L)(2,2-biby)·2H2O] n , obtained by the following steps:

[0059] 0.2 mol of 2-(3-carboxyphenyl)-6-carboxybenzimidazole L, 0.3 mol of 2,2-biby, 0.4 mol of Co(NO3)2·4H2O, 50 mL of deionized water and 50 mL of acetonitrile were mixed evenly, sealed and stirred for 30 min at room temperature, pH was adjusted to 7 with 0.5 mol / L NaOH, and stirred for another 30 min. The obtained suspension was transferred to a polytetrafluoroethylene reactor (150 mL), covered with an inner cover and placed in a high-pressure stainless steel reactor. The high-pressure reactor was heated to 140°C in a programmable temperature-controlled oven and kept warm for 72 hours. The reaction solution was then heated at 5°C·h -1 The mixture was cooled to room temperature at a rate of to obtain a cobalt transition metal coordination polymer.

[0060] The cobalt transition metal coordination polymer prepared in Example 1 was characterized to obtain the crystallographic parameters shown in Table 1 and the partial bond length and bond angle data shown in Table 2. The elemental analysis theoretical values ​​of the complex are C: 56.45, H: 3.76, N: 10.54 (derived from CCDC: 2384213), and the experimental values ​​are C: 55.75, H: 3.43, N: 10.15.

[0061] Table 1 Crystallographic parameters of the complexes

[0062]

[0063] *R=∑(F o –F c ) / ∑(F o ); **wR2={∑[w(F o 2 –F c 2 ) 2 ] / ∑(F o 2 ) 2} 1 / 2 .

[0064] Table 2 Partial bond lengths of complexes and bond angle (°)

[0065]

[0066] Symmetric code: A:x,1+y,z.

[0067] The cobalt metal organic coordination polymer prepared in Example 1 was tested (the following tests are all based on the cobalt metal organic coordination polymer in Example 1), and its asymmetric environment diagram is as follows Figure 1 As shown by Figure 1 It can be seen that the cobalt metal organic coordination polymer has the advantages of high coordination number, multi-center coordination, asymmetric environment and multifunctionality. Its 1D chain structure is as follows Figure 2 As shown in the figure, it can be seen that the 1D chain structure of the cobalt metal organic coordination polymer has the advantages of high stability, good conductivity, high specific surface area, adjustable pore structure and easy synthesis.

[0068] The cobalt transition metal coordination polymer prepared in Example 1 was subjected to thermogravimetric analysis. Figure 3 As shown, the thermogravimetric curve of the polymer is: Thermogravimetric analysis of the cobalt transition metal coordination polymer sample was performed under N2 conditions. The cobalt transition metal coordination polymer has a small amount of weight loss in the range of 201.6-251.9℃, which is the weight loss of the coordinated water molecules. When the temperature rises above 342.6℃, the organic ligands in the cobalt transition metal coordination polymer begin to decompose, and the overall skeleton of the organic ligand molecules in the molecule begins to collapse, and finally decomposes into metal oxides.

[0069] Figure 4 The experimental test and computer-simulated X-ray powder diffraction patterns of the cobalt transition metal coordination polymer prepared in Example 1 are compared with the theoretical simulated powder XRD pattern of the sample and the experimental data test pattern. The results show that the peak shape and position of the theoretical data pattern and the experimental measured pattern are consistent in the range of 2θ of 5-50°. At the same time, it is consistent with the elemental analysis results of the sample, indicating that the sample of the synthesized complex is pure phase.

[0070] Figure 5 This is the infrared spectrum test chart of the cobalt transition metal coordination polymer prepared in Example 1. -1 The broad absorption peak at 1601 cm is the absorption peak of OH in coordinated water in the coordination polymer. -1 The absorption peak at 1562 cm is the C=O double bond stretching vibration of the carboxylate in 2-(3-carboxyphenyl)-6-carboxybenzimidazole. -1 The absorption peak near 1386cm is the stretching vibration of the C=N double bond on the auxiliary 2,2'-bipyridine ring. -1 The peaks at 796 and 718 cm are for the bending vibration of COC, and the peaks for the out-of-plane bending vibration of CH are at 796 and 718 cm, respectively. -1 nearby.

[0071] The photocatalytic properties of the cobalt transition metal coordination polymer prepared in Example 1 were tested to see whether it was a potential photocatalyst for catalytic degradation of organic pollutants in water. The photocatalytic degradation of organic dyes was performed as follows: 25 mg of the sample was finely ground and added to an aqueous solution of naphthol green B, amaranth or algae red B and stirred to achieve adsorption-desorption equilibrium. The mixed solution was then placed under an ultraviolet Hg lamp and stirred, and 5 mL of the solution was taken out every 5 minutes.

[0072] The aqueous solutions of organic dyes naphthol green B, amaranth or erythrosine B were selected to explore the photocatalytic activity of cobalt transition metal coordination polymer samples. Figure 6 , Figure 7 and Figure 8 These are the photocatalytic UV spectra of cobalt transition coordination polymers on aqueous solutions of naphthol green B, amaranth and erythrophyll B. Under ultraviolet light, the ultraviolet absorption peaks of these three dyes weakened significantly with time. The results show that the catalyst has strong photocatalytic degradation ability for naphthol green B, amaranth and erythrophyll B, especially erythrophyll B.

[0073] like Fig. 9 As shown, according to the solution concentration C / C0 calculation (C is the absorption peak intensity at a certain time, C0 is the absorption peak intensity of the initial concentration), the photocatalytic degradation rate of erythrophyll B by the cobalt transition metal coordination polymer is 93.5% (the self-degradation rate of erythrophyll B is 45.1%); the photocatalytic degradation rate of amaranth red by the cobalt transition metal coordination polymer is 38.1%; the photocatalytic degradation rate of naphthol green by the cobalt transition metal coordination polymer is 36.1%; the results show that the cobalt transition metal coordination polymer has a good photocatalytic degradation effect on the three dyes, especially on erythrophyll B.

[0074] The catalytic mechanism of cobalt transition metal coordination polymer in phycoerythrocyanine B was also tested. The tert-butyl alcohol (TBA) scavenger of ·OH, ammonium oxalate (AO) scavenger of photogenerated holes and ·O2 - The capture agent benzoquinone (BQ)

[0075] like Fig.10 and Fig.11 As shown in the figure, according to the solution concentration C / C0, the degradation rate of erythrocyanide B is 93.5% without the three capture agents, 87.5% with TBA, 90.1% with AO, and 49.3% with BQ. By comparing the data in the presence of different capture agents, it is concluded that the photodegradation of erythrocyanide B is caused by·O2 - Free radical dominated.

[0076] like Fig.12 As shown in the figure, the kinetic study test shows that with Ln(C0 / C) as the ordinate and reaction time t as the abscissa, the linear coefficient of the function graph is 0.9962, which indicates that the degradation reaction of cobalt transition metal coordination polymer to phycoerythrocyanine B conforms to the first-order kinetic reaction characteristics, and the rate constant of the degradation reaction within 20 minutes is 0.1303min -1 .

[0077] The catalyst reusability test was carried out on the cobalt transition metal coordination polymer, such as Fig.13As shown. After the degradation reaction, the cobalt transition metal coordination polymer was centrifuged, washed and dried, and used for the next degradation of erythrophycoerythrophyll B. The experimental results showed that after four cycles of use, the catalytic activity of the cobalt transition metal coordination polymer did not significantly degrade, indicating that the cobalt transition metal coordination polymer has a high reuse rate.

[0078] In summary, the photocatalytic degradation rate of the cobalt metal organic complex material prepared by the present invention for erythrocyanine B within 20 minutes is 93.5% (the self-degradation rate of blank erythrocyanine B is 45.1%); the photocatalytic degradation rate of amaranth is 38.1%; and the photocatalytic degradation rate of naphthol green is 36.1%. The photocatalytic degradation of organic dyes by cobalt metal organic complexes is compared. The cobalt metal organic complex material catalyst has the best photocatalytic degradation performance for erythrocyanine B, and can be used as a potential photocatalyst to catalyze the degradation of organic pollutants in water.

[0079] Therefore, the present invention adopts the above-mentioned cobalt transition metal coordination polymer and its preparation method and application. The cobalt transition metal coordination polymer has good photocatalytic performance and can be used as a potential photocatalyst to catalyze the degradation of organic pollutants in water.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A cobalt transition metal coordination polymer, characterized in that: The chemical formula of cobalt transition metal coordination polymer is: [Co(L)(2,2-biby)·2H2O] n ; Wherein, L is 2-(3-carboxyphenyl)-6-carboxybenzimidazole; 2,2-biby is 2,2'-bipyridine; n represents the degree of polymerization, which is a positive integer; and the cobalt transition metal coordination polymer belongs to the orthorhombic system and the P212121 space group.

2. A cobalt transition metal coordination polymer according to claim 1, characterized in that: The basic structural unit of cobalt transition metal coordination polymers consists of a metal Co 2+ , 1 coordinated 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 1 coordinated 2,2'-bipyridine, and 2 coordinated water molecules; 2-(3-carboxyphenyl)-6-carboxybenzimidazole adopts a monodentate coordination mode with the metal Co through the carboxyl groups at both ends 2+ Coordination, 2,2'-bipyridine with metal Co 2+ Bidentate chelate coordination, water molecules adopt monodentate coordination mode with metal Co 2+ Coordination.

3. A cobalt transition metal coordination polymer according to claim 2, characterized in that: 1 metal Co 2+ Denoted as Co1, it forms a six-coordinated deformed octahedral configuration with two coordinated oxygen atoms O2 and O3A of two 2-(3-carboxyphenyl)-6-carboxybenzimidazoles, two coordinated nitrogen atoms N1 and N2 of one 2,2'-bipyridine, and two coordinated water molecules O1W and O2W; O3A, O2, N1 and N2 occupy the four equatorial vertices of the deformed octahedral configuration, and O1W and O2W occupy the two vertex positions of the deformed octahedral configuration; the bond length of Co-O in the deformed octahedral configuration is The bond length of Co-N is The bond angle of O-Co-O is 85.25(9)~171.61(10)°, and the bond angle of O-Co-N is 90.36(10)~173.28(10)°.

4. A cobalt transition metal coordination polymer according to claim 3, characterized in that: Adjacent metal Co 2+ By connecting with 2-(3-carboxyphenyl)-6-carboxybenzimidazole ligands, a 1D chain structure is formed, and the 1D chain structure is expanded into a three-dimensional network structure through weak interaction forces.

5. A cobalt transition metal coordination polymer according to claim 4, characterized in that: The weak interaction force is one or more of π-π stacking, OH...O hydrogen bonding, OH...N hydrogen bonding and CH...O hydrogen bonding.

6. A method for preparing a cobalt transition metal coordination polymer as claimed in claim 5, characterized in that: The following steps are involved: S1. Dissolve 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 2,2'-bipyridine and Co(NO3)2·4H2O in deionized water and acetonitrile, and stir in a sealed container at room temperature; S2. Add NaOH to adjust pH to 5-7 and continue stirring for 25-35 minutes; S3, transferring the obtained suspension to a polytetrafluoroethylene reactor, covering it with an inner cover and placing it in a high-pressure stainless steel reactor, heating the high-pressure reactor in a programmable temperature-controlled oven and keeping it warm for culturing; S4, the reaction solution was heated at 3-7℃·h -1 The reaction mixture is cooled to room temperature at a rate of , and a cobalt transition metal coordination polymer is obtained.

7. The method for preparing a cobalt transition metal coordination polymer according to claim 6, characterized in that: The molar ratio of 2-(3-carboxyphenyl)-6-carboxybenzimidazole, 2,2'-bipyridine and Co(NO3)2·4H2O in S1 is 1:0.5:1-1:3:4, and the sealed stirring time is 25-35 min.

8. The method for preparing a cobalt transition metal coordination polymer according to claim 6, characterized in that: The high pressure reactor in S3 is heated to 100-140°C and the temperature is kept constant for 36-72 hours.

9. An application of a cobalt transition metal coordination polymer, characterized in that: The cobalt transition metal coordination polymer described in claim 5 is used for photocatalytic degradation of organic pollutants in water.

Citation Information

Patent Citations

  • Organic rhodamine B and inorganic Cr (VI) bifunctional visible light catalytic degradation organic complex as well as preparation method and application of organic rhodamine B and inorganic Cr (VI) bifunctional visible light catalytic degradation organic complex

    CN114950560A

  • Manganese transition metal coordination polymer as well as preparation method and application thereof

    CN117164876A

  • Double thermal healthcare band with light therapy function

    KR1020250050421A

  • Organometallic Framework Materials of Transition Group III

    US20080300387A1

  • Metal complexes of substituted 4-(2-carboxy-phenylazo-5-pyrazolones

    US4847365A

Cited By

  • Anti-corrosion coating material based on metal coordination structure as well as preparation method and application of anti-corrosion coating material

    CN120665516A